Comparison of Presentation, Course, and Outcome of Congenital and Acquired Cytomegalovirus Infection in Twins - Veronica Mugarab Samedi; Christopher Skappak; Lindsay Jantzie; Cynthia Trevenen; Majeeda Kamaluddeen; Pauline Ekwalanga; Essa Hamdan Al Awad (Thieme Medical Publishers, Inc., 2016)
Abstract Background Cytomegalovirus (CMV) is one of the most common causes of serious viral intrauterine infections. It is universally distributed among the human population with an average incidence of 0.15 to 2%. Indeed, at least half of the women in the reproductive age have evidence of prior CMV infection. Epidemiology and Pathogenicity However, it is not a usual practice to screen asymptomatic pregnant woman or neonates for CMV. Even if a mother developed a primary CMV infection during pregnancy, up to 90% of the newborns with congenital CMV will be asymptomatic at the time of birth. Only 5 to 7% of the infected babies will be acutely symptomatic, and the typical clinical presentation includes intrauterine growth restriction, microcephaly, various cutaneous manifestations (including petechiae and purpura), hematological abnormalities (particularly resistant thrombocytopenia), hepatosplenomegaly, chorioretinitis, hepatitis, etc. In contrast, acquired CMV infection is extremely unlikely to cause any serious sequelae for the infant. Cases  We present a case of congenital and acquired CMV infection in twins with a focus of dissimilarity in presentation, clinical course, and outcome.